Economic policy supporting social well-being. Remarks on the margin of Ludwig Erhard’s book “Prosperity for All” - Łuszczyk, Marcin (Rozwój Regionalny i Polityka Regionalna, 2020)
The purpose of the article is to present the achievements of Ludwig Erhard in the field of economic policy and his vision of social well-being. Immediately after World War II, Erhard was the main author of Germany’s economic policy. Based on the principles of ordoliberalism, the social market economy became the source of economic success. Under the Constitution, also in Poland the social market economy forms the basis of the economic system. However, it turns out that the actions taken differ significantly from Erhard’s original concept, and sometimes even close to the model of the socialist economic order. The state’s interference in market processes is growing, ad hoc decisions are more and more often made, calculated more to improve the current situation than to ensure lasting prosperity.